Minimally Invasive Direct In-situ Magnetic Loss Measurement in Power Electronic Circuits - Yi, Lifang; McTigue, Mike; Gines, David; Doerr, Brad; Moon, Jinyeong (IEEE transactions on power electronics, 2023)
Designing a good magnetic component is essential for achieving high efficiency in power converters. However, validating such a design is difficult, especially when the power converter operates in the desired condition. Accurate direct in-situ magnetic loss measurement has been known as unattainable due to an unknown timing skew between measurement channels. The unavoidable timing skew, arising from various reasons, can introduce highly excessive measurement errors, rendering the direct in-situ loss measurement unfit to be used in reality. This paper proposes a novel method to eliminate the errors associated with the timing skew and make the accurate, direct, and in-situ magnetic loss measurement practical and minimally invasive. The new method, termed as improved Dual-curve Derivative method, is introduced and analyzed in detail based on mathematical models. Compared to the existing methods, the novel method achieves more accurate measurements while reducing invasiveness to the power converter. The operational principles and performance of the improved Dual-curve Derivative method are verified in simulation and validated in experiments in a DC-DC step-down buck converter, subject to various realistic circuit parameters.